Kinetic study on ferulic acid production from banana stem waste via mechanical extraction - Muhamad Khairi, Jusup (2017)
Banana which is the herbaceous plants from the genus Musa are well known to be the plants that associated with many medicinal properties. Banana has been reported to be a potent source of phenolic compounds and one of the important compounds in this plant is ferulic acid (FA). Ferulic acid has excellent antioxidant properties which are higher than those of vitamin C and E. It also have a wide range of biological activities, such as antioxidant activities, protection against coronary heart diseases, anti-inflammatory , anti-tumour , anti-mutagenic, anti-carcinogenic and anti-microbial activities. In this study, the work deals with the mechanical extraction of banana stem by using sugar cane press machine for the extraction of ferulic acid (FA). The objectives of this study is to determine the kinetic parameters in the ferulic acid production. The banana sample was collected randomly from the local banana plantation in Felda Lepar Hilir, Pahang. The banana stem juice was extracted by using sugarcane press machine (KR3176) with three rotating cylinder rolling. The extracted juice was then analysed by using high performance liquid chromatography (HPLC) in order to quantify the yield of FA that has been extracted. The integral method was proposed in this study in order to find the kinetic parameter of the extraction process and the data obtained were fitted into the 0th, 1st and 2nd order extraction process. Based on the results, the kinetic parameter and R2 value from this research were 0.05 and 0.93 respectively. In this research, it was found that the 0th order extraction process was the most suitable reaction order to represent the behavior of this extraction process. This is due to this extraction process does not involves any usage of chemicals as reactants or catalyst.